Faktor-faktor yang mempengaruhi laba pada usaha ikan asin di Kelurahan Kampung Baru Kecamatan Rumbia Tengah Kabupaten Bombana - Andyani, Mery; Budiyanto; Mansyur, Akhmad (Jurnal Sosial Ekonomi Perikanan, 2021)
Profit model is important to undertake to determine factors affected a business future through maintaining sustainable profitability. The aim of this research was to determine factors that affected and their magnitude toward the profit of salted fish mini plant in Kampung Baru Village of Central Rumbia, Bombana District South East Sulawesi. This research was conducted from November to December 2018. The samples were 20 respondents of salted fish plant owner as a primary data source. Data collected included profit, capital productivity, and labor productivity. The data obtained were analyzed using linear regression models. The results showed that capital and labor productivity was the main factors affecting profit of the salted fish plant. The magnitude effect of each factor was 2,623 and 1,981 for capital and labor productivity, respectively. Therefore to maintain profit and thus the sustainable of the plant, every change from these variables should be taken into account when making business decision.